Optimalisasi Pengelolaan Keuangan Publik : Peran BUMN, Lembaga Negara, dan Literasi Masyarakat - Indana Zahratul Auliya; Qayyis Ainu Rahmatika; Rosiah; Muhammad Budi Utama (Journal of Public Sector Financial Management, 2026)
Public financial management plays a crucial role in supporting the realization of transparent and accountable governance. This article aims to examine the contribution of State-Owned Enterprises (SOEs), government institutions, and the level of public financial literacy in optimizing public financial management. This research employs a literature study method by analyzing various scientific sources, government documents, and relevant regulations. The findings indicate that collaboration among SOEs, government institutions, and communities with adequate financial literacy contributes significantly to improving efficiency, transparency, and accountability in public finance. Therefore, strengthening institutional roles and enhancing public financial literacy should be the primary focus in public policy formulation.